2020
DOI: 10.1101/2020.06.16.155515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative mapping of mRNA 3’ ends inPseudomonas aeruginosareveals a pervasive role for premature 3’ end formation in response to azithromycin

Abstract: P. aeruginosa produces serious chronic infections in hospitalized patients and immunocompromised individuals, including cystic fibrosis patients. The molecular mechanisms by which P. aeruginosa responds to antibiotics and other stresses to promote persistent infections may provide new avenues for therapeutic intervention. Azithromycin (AZM), an antibiotic frequently used in cystic fibrosis treatment, is thought to improve clinical outcomes through a number of mechanisms including impaired biofilm growth and QS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 151 publications
(334 reference statements)
0
3
0
Order By: Relevance
“…The quorum sensing regulatory gene rhlR is more vulnerable to the translational repression by azithromycin owing to its rare codon ( Gödeke et al., 2013 ), thus leading to the repression of quorum sensing regulated virulence factors and subsequent inhibition of biofilm formation or disruption of biofilm. A recent study revealed that azithromycin induces changes in the 3′ end formation of mRNAs in P. aeruginosa , which results in repression of genes related to quorum sensing, biofilm formation, and stress responses ( Konikkat et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The quorum sensing regulatory gene rhlR is more vulnerable to the translational repression by azithromycin owing to its rare codon ( Gödeke et al., 2013 ), thus leading to the repression of quorum sensing regulated virulence factors and subsequent inhibition of biofilm formation or disruption of biofilm. A recent study revealed that azithromycin induces changes in the 3′ end formation of mRNAs in P. aeruginosa , which results in repression of genes related to quorum sensing, biofilm formation, and stress responses ( Konikkat et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, gacS has been shown to be involved in the switch from a hyperadherent small colony phenotype back to a wild type phenotype indicating that loss of GacS function is beneficial in biofilms (Davies et al 2007). The additional two biofilm specific loci, PA14_13150 and PA14_71750, are less understood transcriptional regulators, however PA14_71750 has been previously associated with biofilm adaptation in Pseudomonas (Konikkat et al 2020).…”
Section: Targets Of Selectionmentioning
confidence: 99%
“…This conserved GTPase is known to be associated with persister formation in different bacteria, therefore directly or indirectly plays a role in antibiotic resistance. In clinically important organism, Pseudomonas aeruginosa (associated with cystic fibrosis) the expression of full length Obg transcript is enhanced significantly whereas different other genes including those are involved in exerting virulence property has been prematurely terminated in presence of macrolide azithromycin (Konikkat et al, 2021). As Obg has structural interaction with alarmone ppGpp that controls the gene expression under stringent condition by relieving the pause of RNA polymerase across the length of gene, helps in the up‐regulation of obg transcript.…”
Section: Introductionmentioning
confidence: 99%